Des Hauts de Hurlevent à Onimaru - Michel Naumann; Natalia Naydenova (Cahiers Victoriens et Edouardiens)
The article deals with the analysis of Onimaru, a Japanese film version of Wuthering Heights by E. Brontë. A study of transplantation of a literary work into a different culture suggests a new perception of the initial creation and reveals its most unexpected aspects. Based on three approaches (music, image, protagonists), this paper aims at explaining how Japanese traditional beliefs, which are at the heart of the film, allow a better understanding of a Victorian novel.